ZİYA GÖKALP AND THE SIMPLIFICATION OF LANGUAGE - Özbek, Betül Hastaoğlu (Van Yüzüncü Yıl Üniversitesi, 2024)
Ziya Gökalp is one of the figures who is considered to be a cornerstone in Turkish literature as an ideologist, writer, thinker and poet. Language, which plays an active role in the proper shaping and transmission of the nation's genetic codes, is the most important issue for Ziya Gökalp. It is the main source of culture, history and art, and the main material of thought. Languages that lose their simplicity and are overly exposed to external influences are doomed to disappear over time. Gökalp is aware of the fact that nations that lose their language will disintegrate and disappear from the stage of history, and is conscious of the need to preserve Turkish and restore it to its former simplicity. Facing the fear of Turkish being forgotten drives him to think and work on language. In this respect, he joins the Yeni Lisan movement by taking part with the writers of Genç Kalemler magazine who share the same concerns with him. In his own works, he successfully followed the path he determined for the homeland to attain a national language, plain Turkish, free from the influence of foreign languages as much as possible. The author, with his efforts that seem to be aimed at the simplification of the language in theory, in reality aimed for the society to have a new view of life. In this article titled "Ziya Gökalp and the Importance of Language", the simplification process of Turkish is explained briefly and Ziya Gökalp's contributions to the process are presented through the ideas he expressed in his works and his poems.

Ziya Gökalp, ideolog, yazar, düşünür ve şairlik yönleriyle Türk edebiyatında mihenk taşı kabul edilen isimlerden biridir. Milletin genetik kodlarının doğru şekillenmesi ve aktarılmasında aktif bir rol oynayan dil, Ziya Gökalp’ın en önemli meselesi durumundadır. Kültür, tarih, sanat gibi unsurların kaynaştırıcı ve güçlendirici ögesi, düşüncenin ana malzemesidir. Dış etkilere aşırı maruz kalan ve sadeliğini yitiren diller, zamanla yok olmaya mahkumdur. Gökalp, dilini kaybeden milletlerin dağılıp tarih sahnesinden silineceği gerçeğinin farkında, Türkçenin korunup eski sadeliğine kavuşturulması gerektiğinin bilincindedir. Türkçenin unutulması endişesiyle yüzleşmek, onu dil üzerine düşünüp çalışmaya yöneltir. Bu minvalde, kendisiyle aynı hassasiyeti taşıyan Genç Kalemler dergisi yazarlarının yanında yer alarak Yeni Lisan hareketine katılır. Vatanın, yabancı dillerin etkisinden mümkün olduğunca arınmış millî bir dile, sade Türkçeye kavuşması için belirlediği yolu, kendi eserlerinde başarıyla takip etmiştir. Sanatçı, teoride dilin sadeleştirilmesini amaçlar gibi görünen çabalarıyla aslında toplumun yeni bir hayat görüşüne sahip olmasını hedeflemiştir. “Ziya Gökalp ve Dilin Önemi” başlıklı bu makalede, Türkçenin sadeleşme sürecinden kısaca bahsedilerek Ziya Gökalp’ın sürece olan katkıları, eserlerinde belirttiği düşünceler ve şiirleri üzerinden dile getirilmiştir.
Ziya Gökalp ve Dilin Sadeleşmesi
Keywords: Turkish Language and Literature (Other); Türk Dili ve Edebiyatı (Diğer)